Sustainable nitrogen fixation: Agrochemical research in food production adapted to planetary limits - Lluís Pascual; Emanuela Accardo; Hermenegildo Garcia Baldoví (Mètode Science Studies Journal: Annual Review, 2024)
Today's global food production depends on the fixation of atmospheric nitrogen by using the Haber-Bosch process. The application of this catalytic system laid the foundations for the development of industrial agriculture and led to an unprecedented acceleration in the growth of human societies during the so-called Green Revolution. However, this production model does not appear to be able to adapt to the current challenges of energy sustainability and climate crisis response. The Haber-Bosch cycle has a major impact on energy consumption and carbon dioxide emissions. In order to rethink this agri-food model, this article examines chemical and technological development strategies to move towards an energy and environmentally sustainable model.